Composite positive electrode material and preparation method and application thereof

The liquid phase coating is formed on the surface of the high-nickel positive electrode material, which solves the problem of the degradation of the stability and circulation performance of the high-nickel positive electrode material during the circulation process, significantly reduces the surface residual alkali, slows down side reactions, and improves thermal stability and circulation performance.

CN119674001APending Publication Date: 2025-03-21TIANJIN B&M SCI & TECH LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411842685.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

During the circulation process, high-nickel positive electrode materials have more Li+ and produce strong oxidizing N4+, resulting in a decrease in the stability and circulation performance of the material. At the same time, it is difficult to control impurities of lithium carbonate and lithium hydroxide during synthesis and storage, resulting in an increase in the residual alkali on the surface and affecting the battery performance.

Method used

A uniform perovskite phase coating is formed on the surface of the matrix material by liquid phase coating, which significantly reduces the residual alkali on the surface, slows down the side reactions on the surface of the material, and improves the thermal stability and cycling performance of the composite positive electrode material.

Benefits of technology

It has achieved significant reduction of surface residual alkali, slowed down side reactions, improved thermal stability and cycling performance, and improved the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005188308760000161
    Figure BDA0005188308760000161
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a composite positive electrode material and a preparation method and application thereof. The composite positive electrode material comprises a base material and a perovskite phase coating layer coating the surface of the base material, the chemical formula of the base material comprises LiNi < x > Co < y > Mn < 1-x-y-z > M < z > O < 2 >, 1, 0 < = y < lt >; 0 < = zlt; 0.2, x + y + zlt; 1, the chemical formula of the perovskite phase coating layer comprises AQO3, A is at least one of Ca, Sr and Ba, and Q is Ti or Zr. According to the composite positive electrode material, the uniform perovskite phase coating layer is arranged on the surface of the base material, so that the surface residual alkali can be remarkably reduced, the side reaction on the surface of the material is slowed down, and the thermal stability and the cycle performance of the composite positive electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a composite positive electrode material and a preparation method and application thereof. Background Art

[0002] High nickel cathode material is one of the most promising new generation cathode materials. Over the years, people have gradually increased the Ni content in NCM and NCA cathodes while reducing the Co content to increase their capacity and reduce costs. However, as the Ni content increases, high nickel cathode materials will release more Li + , generating more strongly oxidizing N 4+ , which reduces the stability of the positive electrode / electrolyte interface of the material, deteriorates the thermal stability, and affects the cycle performance of the battery. At the same time, during the synthesis and storage of high-nickel positive electrode materials, lithium carbonate and lithium hydroxide impurities are difficult to control, resulting in an increase in surface residual alkali: on the one hand, the electrolyte decomposes, causing the battery to produce gas; on the other hand, the slurry is easily turned into a jelly-like state during the coating process, which is not conducive to battery production.

[0003] During the cycle of high-nickel positive electrode materials, the exothermic reaction between the oxygen precipitated from the positive electrode and the electrolyte causes local heat accumulation in the material. This local heat accumulation will make the surface side reactions of the positive electrode material more serious, resulting in irreversible interface failure. During the preparation process of high-nickel positive electrode materials, excessive lithium sources are usually added to obtain completely crystallized positive electrode materials. Therefore, more residual lithium is formed during the cooling and unloading stages, making the electrode slurry prepared using the high-nickel ternary positive electrode material prone to gelation, causing coating difficulties, and at the same time aggravating the release of gas during the battery cycle, resulting in reduced electrochemical performance of the battery.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] One object of the present invention is to provide a composite positive electrode material, which can significantly reduce the surface residual alkali, slow down the side reactions on the material surface, and improve the thermal stability and cycle performance of the composite positive electrode material by forming a uniform perovskite phase coating layer on the surface of the base material through liquid phase coating.

[0006] Another object of the present invention is to provide a method for preparing a composite positive electrode material, which is simple and easy to implement, environmentally friendly, can reduce residual alkali, improve the thermal stability of the positive electrode material, inhibit the release of oxygen, and improve the cycle performance of the positive electrode material.

[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0008] A composite positive electrode material, comprising a base material and a perovskite coating layer coated on the surface of the base material; the chemical formula of the base material comprises LiNi x Coy Mn 1-x-y-z M z O 2 , wherein 0.8≤x<1, 0≤y<0.2, 0≤z<0.2, x+y+z<1, M comprises at least one of Al, Sb, Sn, B, Na, Mg, Ca, Ti, V, Zn, Si, Sr, Y, Zr, Nb, Mo, Ta, W, La, Pr, Nd and Eu; the chemical formula of the perovskite phase coating layer comprises AQO 3 , A is at least one of Ca, Sr and Ba, and Q is Ti or Zr.

[0009] In some embodiments, the mass of the perovskite phase coating layer accounts for 0.1% to 5% of the mass of the composite positive electrode material.

[0010] In some embodiments, the particle size D50 of the matrix material is 5 to 16 μm.

[0011] In some embodiments, the capacity retention rate of a battery prepared from the composite positive electrode material after 50 cycles at 45° C., 1C charge and discharge, and 2.5 to 4.25V is greater than or equal to 94.5%.

[0012] A method for preparing a composite positive electrode material comprises the following steps:

[0013] Obtain a mixture of nickel-cobalt-manganese hydroxide, a compound of element M and a lithium source, wherein the element M source includes at least one of Al, Sb, Sn, B, Na, Mg, Ca, Ti, V, Zn, Si, Sr, Y, Zr, Nb, Mo, Ta, W, La, Pr, Nd and Eu; perform a first heat treatment on the mixture to obtain a matrix material; obtain a mixed solution of a compound of element A, a compound of element Q and water, wherein A is at least one of Ca, Sr and Ba, and the element Q is Ti or Zr; mix the mixed solution with the matrix material, perform solid-liquid separation, collect the solid and perform a second heat treatment.

[0014] In some embodiments, the chemical formula of the nickel-cobalt-manganese hydroxide is Ni x Co y Mn 1-x-y-z R z (OH) 2 , 0.8≤x<1, 0≤y<0.2, 0≤z<0.2, x+y+z<1, and R includes at least one of Al, Y, B, Mg, Ti, Zr, Si, Nb, Mo and La.

[0015] In some embodiments, the molar ratio of the nickel-cobalt-manganese hydroxide, the lithium source and the compound of element M is 1:(1-1.1):(0.005-0.02).

[0016] In some embodiments, the first heat treatment includes a first calcination and a second calcination performed sequentially; the temperature of the first calcination is 450-600°C, and the constant temperature time is 3-9 hours; the temperature of the second calcination is 650-800°C, and the constant temperature time is 10-20 hours; the heating rates of the first calcination and the second calcination are each independently 1.5-5°C / min.

[0017] In some embodiments, the first heat treatment is performed under an atmosphere containing oxygen.

[0018] In some embodiments, the mass ratio of the total mass of the compound of element A and the compound of element Q to the matrix material is (3-8):500.

[0019] In some embodiments, the mass ratio of the compound of element A, the compound of element Q and water is (1.2-3):(1-6):(180-220).

[0020] In some embodiments, the compound of element A includes at least one of a nitrate and an acetate of element A.

[0021] In some embodiments, the compound of element Q includes at least one of an inorganic compound of element Q and an acetate.

[0022] In some implementations, the mixed solution and the matrix material are mixed for a period of 10 seconds to 30 minutes.

[0023] In some embodiments, the temperature of the second heat treatment is 500-800° C., the heating rate is 1.5-6.0° C. / min, and the constant temperature time is 1-8 hours.

[0024] In some embodiments, the second heat treatment is performed under an oxygen-containing atmosphere.

[0025] In some embodiments, before the second heat treatment, the solid is dried at a temperature of 60 to 200° C. and for a time of 1 to 6 hours.

[0026] A battery comprises the composite positive electrode material, or the composite positive electrode material prepared by the method for preparing the composite positive electrode material.

[0027] An electrical device comprises the battery.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The composite positive electrode material of the present invention forms a uniform perovskite phase coating layer on the surface of the base material by liquid phase coating, which can significantly reduce the residual alkali on the surface, slow down the side reactions on the surface of the material, and improve the thermal stability and cycle performance of the composite positive electrode material.

[0030] (2) The preparation method of the composite positive electrode material of the present invention uses a mixed solution containing perovskite phase elements for liquid phase coating, which can remove residual alkali and achieve uniform coating of the perovskite phase, thereby stabilizing and protecting the surface of the base material; compared with solid phase coating, the coating layer formed by liquid phase coating is more uniform and can significantly reduce residual alkali; compared with conventional water washing, liquid phase coating can remove residual alkali and form a coating layer on the surface of the base material, thereby improving the thermal stability of the positive electrode material, inhibiting the release of oxygen, and improving the cycle performance of the positive electrode material.

[0031] (3) The battery of the present invention has excellent high temperature performance. DETAILED DESCRIPTION

[0032] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0033] According to one aspect of the present invention, the present invention relates to a composite positive electrode material, comprising a base material and a perovskite phase coating layer coated on the surface of the base material; the chemical formula of the base material comprises LiNi x Co y Mn 1-x-y-z M z O 2 , wherein 0.8≤x<1, 0≤y<0.2, 0≤z<0.2, x+y+z<1, M comprises at least one of Al, Sb, Sn, B, Na, Mg, Ca, Ti, V, Zn, Si, Sr, Y, Zr, Nb, Mo, Ta, W, La, Pr, Nd and Eu; the chemical formula of the perovskite phase coating layer comprises AQO 3 , A is at least one of Ca, Sr and Ba, and Q is Ti or Zr.

[0034] The composite positive electrode material of the present invention forms a uniform perovskite phase coating layer on the surface of the base material through liquid phase coating, which can significantly reduce the surface residual alkali, slow down the side reactions on the material surface, and improve the thermal stability and cycle performance of the composite positive electrode material.

[0035] In some embodiments, the value of x includes 0.8, 0.82, 0.85, 0.88, 0.9, 0.92, 0.95, 0.98 or 0.99, etc. The value of y includes 0, 0.01, 0.02, 0.05, 0.08, 0.1, 0.15 or 0.18, etc. The value of Z includes 0, 0.01, 0.02, 0.05, 0.08, 0.1, 0.15 or 0.18, etc.

[0036] In some embodiments, the mass of the perovskite phase coating layer accounts for 0.1% to 5% of the mass of the composite positive electrode material, such as 0.1%, 0.2%, 0.5%, 0.6%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, or any range between the two. In the composite positive electrode material of the present invention, the perovskite phase coating layer has a suitable mass content, which is more conducive to cooperating with the matrix material and improving the thermal stability and cycle performance of the positive electrode material.

[0037] In some embodiments, the particle size D50 of the matrix material is 5 to 16 μm, such as 5 μm, 8 μm, 10 μm, 12 μm, 13 μm, 16 μm, etc., or any range therebetween. The matrix material has a suitable particle size, which can improve the thermal stability and cycle performance of the positive electrode material.

[0038] In some embodiments, the capacity retention rate of a battery prepared from the composite positive electrode material at 45°C, 1C charge and discharge, and 2.5-4.25V for 50 cycles is greater than or equal to 94.5%, for example, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, etc., or any range value between the two.

[0039] According to another aspect of the present invention, the present invention also relates to a method for preparing a composite positive electrode material, comprising the following steps:

[0040] Obtain a mixture of nickel-cobalt-manganese hydroxide, a compound of element M and a lithium source, wherein the element M source includes at least one of Al, Sb, Sn, B, Na, Mg, Ca, Ti, V, Zn, Si, Sr, Y, Zr, Nb, Mo, Ta, W, La, Pr, Nd and Eu; perform a first heat treatment on the mixture to obtain a matrix material; obtain a mixed solution of a compound of element A, a compound of element Q and water, wherein A is at least one of Ca, Sr and Ba, and the element Q is Ti or Zr; mix the mixed solution with the matrix material, perform solid-liquid separation, collect the solid and perform a second heat treatment.

[0041] The preparation method of the composite positive electrode material of the present invention uses a mixed solution containing perovskite phase elements for liquid phase coating, and while removing residual alkali, achieves uniform coating of the perovskite phase, thereby stabilizing and protecting the surface of the base material; compared with solid phase coating, the coating layer formed by liquid phase coating is more uniform and can significantly reduce residual alkali; compared with conventional water washing, liquid phase coating can form a coating layer on the surface of the base material while removing residual alkali, thereby improving the thermal stability of the positive electrode material, inhibiting the release of oxygen, and improving the cycle performance of the positive electrode material.

[0042] In some embodiments, the chemical formula of the nickel-cobalt-manganese hydroxide is Ni x Co y Mn 1-x-y-z R z (OH) 2 , 0.8≤x<1, x is, for example, 0.8, 0.81, 0.82, 0.85, 0.88, 0.9, 0.92, 0.95, 0.98, etc.; 0≤y<0.2, for example, 0, 0.01, 0.02, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, etc.; 0≤z<0.2, for example, 0, 0.01, 0.02, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, etc.; x+y+z<1, R includes at least one of Al, Y, B, Mg, Ti, Zr, Si, Nb, Mo and La;

[0043] In some embodiments, the lithium source includes LiOH, Li 2 CO 3 and LiNO 3 One or more of .

[0044] In some embodiments, the compound of element M includes at least one of an oxide, a hydroxide, a nitrate, and a chloride of element M.

[0045] In some embodiments, the molar ratio of the nickel cobalt manganese hydroxide, the lithium source and the compound of element M is 1: (1-1.1): (0.005-0.02), for example, 1: 1: 0.005, 1: 1.01: 0.006, 1: 1: 0.008, 1: 1: 0.01, 1: 1: 0.02, etc. The appropriate ratio of the nickel cobalt manganese hydroxide, the lithium source and the compound of element M can ensure the electrochemical performance of the matrix material.

[0046] In some embodiments, the first heat treatment includes a first calcination and a second calcination performed sequentially; the temperature of the first calcination is 450-600°C, such as 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 550°C, 580°C or 600°C, etc., the heating rate is 1.5-5°C / min, such as 1.5°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, and the constant temperature time is 3-9h, such as For example, 3h, 4h, 5h, 6h, 7h, 8h, 9h, etc.; the temperature of the second calcination is 650-800°C, for example, 650°C, 660°C, 680°C, 700°C, 720°C, 750°C, 780°C, 800°C, etc., the heating rate is 1.5-5°C / min, for example, 1.5°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, etc., the constant temperature time is 10-20h, for example, 10h, 12h, 15h, 18h, 20h, etc. And / or, the first heat treatment is carried out under an oxygen-containing atmosphere, and the air intake rate is 100-400L / min, for example, 100L / min, 150L / min, 200L / min, 300L / min, 400L / min, etc. The present invention adopts the combination of appropriate first calcination conditions and second calcination conditions to ensure that the obtained matrix material has a suitable particle size and excellent electrochemical performance.

[0047] In some embodiments, the mass ratio of the total mass of the compound of element A and the compound of element Q to the matrix material is (3-8):500; the mass ratio of the compound of element A, the compound of element Q and water is (1.2-3):(1-6):(180-220). In some embodiments, the compound of element A includes at least one of a nitrate and an acetate of element A. In some embodiments, the compound of element Q includes at least one of an inorganic compound and an acetate of element Q.

[0048] In some embodiments, the mixed solution and the matrix material are mixed for 10s to 30min, such as 10s, 1min, 2min, 5min, 10min, 15min, 20min or 30min. The mixed solution and the matrix material of the present invention are mixed for a suitable time to ensure that the materials are fully mixed, so as to facilitate subsequent operation steps.

[0049] In some embodiments, the temperature of the second heat treatment is 500-800°C, such as 500°C, 520°C, 550°C, 580°C, 600°C, 650°C, 700°C, 750°C, 800°C, etc., and the heating rate is 1.5-6.0°C / min, such as 1.5°C / min, 2°C / min, 3°C / min, 6°C / min, etc. The constant temperature time is 1-8h, such as 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, etc. The second heat treatment is carried out in an oxygen-containing atmosphere, and the air intake rate is 100-400L / min, such as 100L / min, 200L / min, 300L / min, 400L / min, etc. The present invention adopts appropriate second heat treatment conditions to ensure the thermal stability and cycle performance of the final positive electrode material.

[0050] In some embodiments, before the second heat treatment, the solid is dried at a temperature of 60 to 200° C., such as 60° C., 70° C., 0.10° C., 150° C. or 200° C., and a drying time of 1 to 6 hours, such as 1 hour, 2 hours, 3 hours, 5 hours or 6 hours. The present invention removes moisture by suitable drying conditions. A vacuum oven may be used for drying.

[0051] According to another aspect of the present invention, the present invention also relates to a battery, comprising the composite positive electrode material, or the composite positive electrode material prepared by the method for preparing the composite positive electrode material.

[0052] The battery of the present invention has excellent thermal stability and cycle performance.

[0053] In some embodiments, the battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet includes the above-mentioned composite positive electrode material, a conductive agent and a binder.

[0054] According to another aspect of the present invention, the present invention also relates to an electric device, comprising the battery. The electric device of the present invention includes electric vehicles, portable devices, and the like.

[0055] The following is further explained in conjunction with specific embodiments and comparative examples.

[0056] Example 1

[0057] This embodiment provides a method for preparing a composite positive electrode material, comprising the following steps:

[0058] (1) The weighed Ni 0.93 Co 0.04 Mn 0.02 Al 0.01 (OH) 2 , LiOH and Sb 2 O 3Put it into a high-speed mixer and mix it evenly to form a mixed material. 0.93 Co 0.04 Mn 0.02 Al 0.01 (OH) 2 The molar ratio of Sb is 1.03:1. 2 O 3 with Ni 0.93 Co 0.04 Mn 0.02 Al 0.01 (OH) 2 The molar ratio is 0.006: 1. The high mixer speed is 1000r / min, the mixing time is set to 20min, and the mixing is performed twice.

[0059] (2) The mixed material was placed in a sagger, wherein the height of the mixed material in the sagger was 4 cm, and the sagger was placed in a kiln. Under an oxygen atmosphere, the temperature was first increased to 500°C at a heating rate of 2.5°C / min and kept at this temperature for 6 h; then the temperature was increased to 760°C at the same heating rate and kept at this temperature for 15 h. The material was cooled in the kiln, crushed, and sieved to obtain a matrix material (Li) with a particle size D50 of 12 μm. 1.03 Ni 0.924 Co 0.04 Mn 0.02 Al 0.01 Sb 0.006 O 2 ).

[0060] (2) Dissolve 2.6 g of calcium nitrate hexahydrate and 1.8 g of titanium oxysulfide in 200 g of pure water, wash 500 g of the above matrix material in the solution, and then vacuum filter for 1 min. Then put the filter cake into a vacuum oven, and dry it at 150°C and for 90 min, respectively.

[0061] (4) After the dried material was sieved, it was heated to 700°C at a heating rate of 2.5°C / min in an oxygen atmosphere and kept at that temperature for 8 hours. The calcined product was sieved to obtain 0.3wt% CaTiO 3 Uniformly coated composite positive electrode material.

[0062] Example 2

[0063] This embodiment provides a method for preparing a composite positive electrode material, comprising the following steps:

[0064] (1) The weighed Ni 0.93 Co 0.04 Mn 0.02 Al 0.01 (OH) 2 , LiOH and WO 3Put it into a high-speed mixer and mix it evenly to form a mixed material. 0.93 Co 0.04 Mn 0.02 Al 0.01 (OH) 2 The molar ratio of WO is 1.03:1. 3 with Ni 0.93 Co 0.04 Mn 0.02 Al 0.01 (OH) 2 The molar ratio is 0.006: 1. The high mixer speed is 1000r / min, the mixing time is set to 20min, and the mixing is performed twice.

[0065] (2) The mixed material was placed in a sagger, wherein the height of the mixed material in the sagger was 4 cm, and the sagger was placed in a kiln. Under an oxygen atmosphere, the temperature was first increased to 500°C at a heating rate of 2.5°C / min and kept at this temperature for 6 h; then the temperature was increased to 760°C at the same heating rate and kept at this temperature for 15 h. The material was cooled in the kiln, crushed, and sieved to obtain a matrix material (Li) with a particle size D50 of 12 μm. 1.03 Ni 0.924 Co 0.04 Mn 0.02 Al 0.01 W 0.006 O 2 ).

[0066] (3) 1.5 g of calcium acetate and 5.8 g of zirconium acetate solution (Zr, 13%) were dissolved in 200 g of pure water, 500 g of the above-mentioned matrix material was washed in the solution and then vacuum filtered for 1 min. The filter cake was then placed in a vacuum oven at a drying temperature of 150° C. and a drying time of 90 min, respectively.

[0067] (4) After the dried material was sieved, it was heated to 700°C at a heating rate of 2.5°C / min in an oxygen atmosphere and kept at this temperature for 8 hours. The calcined product was sieved to obtain 0.3wt% CaZrO 3 Uniformly coated composite positive electrode material.

[0068] Example 3

[0069] This embodiment provides a method for preparing a composite positive electrode material, comprising the following steps:

[0070] (1) The weighed Ni 0.93 Co 0.04 Mn 0.02 Y 0.01 (OH) 2 , LiOH and SnO 2Put it into a high-speed mixer and mix it evenly to form a mixed material. 0.93 Co 0.04 Mn 0.02 Y 0.01 (OH) 2 The molar ratio of SnO is 1.03:1. 2 with Ni 0.93 Co 0.04 Mn 0.02 Y 0.01 (OH) 2 The molar ratio is 0.006: 1. The high mixer speed is 1000r / min, the mixing time is set to 20min, and the mixing is performed twice.

[0071] (2) The mixed material was placed in a sagger, wherein the height of the mixed material in the sagger was 4 cm, and the sagger was placed in a kiln. Under an oxygen atmosphere, the temperature was first increased to 500°C at a heating rate of 2.5°C / min and kept at this temperature for 6 h; then the temperature was increased to 760°C at the same heating rate and kept at this temperature for 15 h. The material was cooled in the kiln, crushed, and sieved to obtain a matrix material (Li) with a particle size D50 of 12 μm. 1.03 Ni 0.924 Co 0.04 Mn 0.02 Y 0.01 Sn 0.006 O 2 ).

[0072] (3) Dissolve 1.7 g of strontium acetate and 1.3 g of titanium oxysulfide in 200 g of pure water, wash 500 g of the above matrix material in the solution, and then vacuum filter for 1 min. Then put the filter cake into a vacuum oven, and dry it at 150°C and for 90 min, respectively.

[0073] (4) After the dried material was sieved, it was heated to 700°C at a heating rate of 2.5°C / min in an oxygen atmosphere and kept at that temperature for 8 hours. The calcined product was sieved to obtain 0.3wt% SrTiO 3 Uniformly coated composite positive electrode material.

[0074] Example 4

[0075] This embodiment provides a method for preparing a composite positive electrode material, comprising the following steps:

[0076] (1) The weighed Ni 0.93 Co 0.04 Mn 0.02 Y 0.01 (OH) 2 , LiOH and MoO 3 Put it into a high-speed mixer and mix it evenly to form a mixed material.0.93 Co 0.04 Mn 0.02 Y 0.01 (OH) 2 The molar ratio of MoO is 1.03:1. 3 with Ni 0.93 Co 0.04 Mn 0.02 Y 0.01 (OH) 2 The molar ratio is 0.006: 1. The high mixer speed is 1000r / min, the mixing time is set to 20min, and the mixing is performed twice.

[0077] (2) The mixed material was placed in a sagger, wherein the height of the mixed material in the sagger was 4 cm, and the sagger was placed in a kiln. Under an oxygen atmosphere, the temperature was first increased to 500°C at a heating rate of 2.5°C / min and kept at this temperature for 6 h; then the temperature was increased to 760°C at the same heating rate and kept at this temperature for 15 h. The material was cooled in the kiln, crushed, and sieved to obtain a matrix material (Li) with a particle size D50 of 12 μm. 1.03 Ni 0.924 Co 0.04 Mn 0.02 Y 0.01 Mo 0.006 O 2 ).

[0078] (3) 1.4 g of strontium acetate and 3.9 g of zirconium acetate solution (Zr, 13%) were dissolved in 200 g of pure water, 500 g of the above-mentioned matrix material was washed in the solution and then vacuum filtered for 1 min. The filter cake was then placed in a vacuum oven at a drying temperature of 150° C. and a drying time of 90 min, respectively.

[0079] (4) After the dried material was sieved, it was heated to 700°C at a heating rate of 2.5°C / min in an oxygen atmosphere and kept at that temperature for 8 hours. The calcined product was sieved to obtain 0.3 wt% SrZrO 3 Uniformly coated composite positive electrode material.

[0080] Example 5

[0081] This embodiment provides a method for preparing a composite positive electrode material, comprising the following steps:

[0082] (1) The weighed Ni 0.93 Co 0.04 Mn 0.02 Mg 0.01 (OH) 2 , LiOH and Ta 2 O 5 Put it into a high-speed mixer and mix it evenly to form a mixed material.0.93 Co 0.04 Mn 0.02 Mg 0.01 (OH) 2 The molar ratio of Ta is 1.03:1. 2 O 5 with Ni 0.93 Co 0.04 Mn 0.02 Mg 0.01 (OH) 2 The molar ratio is 0.006: 1. The high mixer speed is 1000r / min, the mixing time is set to 20min, and the mixing is performed twice.

[0083] (2) The mixed material was placed in a sagger, wherein the height of the mixed material in the sagger was 4 cm, and the sagger was placed in a kiln. Under an oxygen atmosphere, the temperature was first increased to 500°C at a heating rate of 2.5°C / min and kept at this temperature for 6 h; then the temperature was increased to 760°C at the same heating rate and kept at this temperature for 15 h. The material was cooled in the kiln, crushed, and sieved to obtain a matrix material (Li) with a particle size D50 of 12 μm. 1.03 Ni 0.924 Co 0.04 Mn 0.02 Mg 0.01 Ta 0.006 O 2 ).

[0084] (3) 1.6 g of barium acetate and 1.1 g of titanium oxysulfide were dissolved in 200 g of pure water, 500 g of the above matrix material was washed in the solution and then vacuum filtered for 1 min. The filter cake was then placed in a vacuum oven at a drying temperature of 150° C. and a drying time of 90 min, respectively.

[0085] (4) After the dried material was sieved, it was heated to 700°C at a heating rate of 2.5°C / min in an oxygen atmosphere and kept at this temperature for 8 hours. The calcined product was sieved to obtain 0.3 wt% BaTiO 3 Uniformly coated composite positive electrode material.

[0086] Example 6

[0087] This embodiment provides a method for preparing a composite positive electrode material, comprising the following steps:

[0088] (1) The weighed Ni 0.93 Co 0.04 Mn 0.02 Mg 0.01 (OH) 2 , LiOH and Nb 2 O 5Put it into a high-speed mixer and mix it evenly to form a mixed material. 0.93 Co 0.04 Mn 0.02 Mg 0.01 (OH) 2 The molar ratio of Nb is 1.03:1. 2 O 5 with Ni 0.93 Co 0.04 Mn 0.02 Mg 0.01 (OH) 2 The molar ratio is 0.006: 1. The high mixer speed is 1000r / min, the mixing time is set to 20min, and the mixing is performed twice.

[0089] (2) The mixed material was placed in a sagger, wherein the height of the mixed material in the sagger was 4 cm, and the sagger was placed in a kiln. Under an oxygen atmosphere, the temperature was first increased to 500°C at a heating rate of 2.5°C / min and kept at this temperature for 6 h; then the temperature was increased to 760°C at the same heating rate and kept at this temperature for 15 h. The material was cooled in the kiln, crushed, and sieved to obtain a matrix material (Li) with a particle size D50 of 12 μm. 1.03 Ni 0.924 Co 0.04 Mn 0.02 Mg 0.01 Nb 0.006 O 2 ).

[0090] (3) 1.5 g of barium acetate and 3.7 g of zirconium acetate solution (Zr, 13%) were dissolved in 200 g of pure water, 500 g of the above-mentioned matrix material was washed in the solution and then vacuum filtered for 1 min. The filter cake was then placed in a vacuum oven at a drying temperature of 150° C. and a drying time of 90 min, respectively.

[0091] (4) After the dried material was sieved, it was heated to 700°C at a heating rate of 2.5°C / min in an oxygen atmosphere and kept at that temperature for 8 hours. The calcined product was sieved to obtain 0.3wt% BaZrO 3 Uniformly coated composite positive electrode material.

[0092] Comparative Example 1

[0093] A method for preparing a composite positive electrode material, which differs from Example 1 in that:

[0094] The composite positive electrode material is prepared according to steps (1) and (2) without performing steps (3) and (4).

[0095] Comparative Example 2

[0096] A method for preparing a composite positive electrode material comprises the following steps:

[0097] (1) The weighed Ni 0.93 Co 0.04 Mn 0.02 Al 0.01 (OH) 2 , LiOH and Sb 2 O 3 Put it into a high-speed mixer and mix it evenly to form a mixed material. 0.93 Co 0.04 Mn 0.02 Al 0.01 (OH) 2 The molar ratio of Sb is 1.03:1. 2 O 3 with Ni 0.93 Co 0.04 Mn 0.02 Al 0.01 (OH) 2 The molar ratio is 0.006: 1. The high mixer speed is 1000r / min, the mixing time is set to 20min, and the mixing is performed twice.

[0098] (2) The mixed material was placed in a sagger, wherein the height of the mixed material in the sagger was 4 cm, and the sagger was placed in a kiln. Under an oxygen atmosphere, the temperature was first increased to 500°C at a heating rate of 2.5°C / min and kept at this temperature for 6 h; then the temperature was increased to 760°C at the same heating rate and kept at this temperature for 15 h. The material was cooled in the kiln, crushed, and sieved to obtain a matrix material (Li) with a particle size D50 of 12 μm. 1.03 Ni 0.924 Co 0.04 Mn 0.02 Al 0.01 Sb 0.006 O 2 ).

[0099] (3) Take 500g of the above matrix material (Li 1.03 Ni 0.924 Co 0.04 Mn 0.02 Al 0.01 Sb 0.006 O 2 ), 0.62 g CaO and 0.88 g TiO 2 Put it into a high-speed mixer and mix it evenly to form a mixed material. 1.03 Ni 0.924 Co 0.04 Mn 0.02 Al 0.01 Sb 0.00 6 O2 , CaO and TiO 2 The molar ratio is 1:0.002:0.002. The speed of the high mixer is 1000r / min, the mixing time is set to 20min, and the mixing is performed twice.

[0100] (4) The mixture was heated to 700°C at a heating rate of 2.5°C / min under an oxygen atmosphere and kept at this temperature for 8 hours. The calcined product was sieved to obtain 0.3 wt% CaTiO 3 Coated composite positive electrode material.

[0101] Comparative Example 3

[0102] A method for preparing a composite positive electrode material comprises the following steps:

[0103] (1) The weighed Ni 0.93 Co 0.04 Mn 0.02 Al 0.01 (OH) 2 , LiOH and Sb 2 O 3 Put it into a high-speed mixer and mix it evenly to form a mixed material. 0.93 Co 0.04 Mn 0.02 Al 0.01 (OH) 2 The molar ratio of Sb is 1.03:1. 2 O 3 with Ni 0.93 Co 0.04 Mn 0.02 Al 0.01 (OH) 2 The molar ratio is 0.006: 1. The high mixer speed is 1000r / min, the mixing time is set to 20min, and the mixing is performed twice.

[0104] (2) The mixed material was placed in a sagger, wherein the height of the mixed material in the sagger was 4 cm, and the sagger was placed in a kiln. Under an oxygen atmosphere, the temperature was first increased to 500°C at a heating rate of 2.5°C / min and kept warm for 6 hours; then the temperature was increased to 760°C at the same heating rate and kept warm for 15 hours. After cooling in the furnace, crushing, and sieving, a high nickel ternary positive electrode material (Li) with a particle size D50 of 12 μm was obtained. 1.03 Ni 0.924 Co 0.04 Mn 0.02 Al 0.01 Sb 0.006 O 2 ).

[0105] (3) Take 500g of the above high nickel ternary positive electrode material (Li 1.03 Ni 0.924 Co 0.04 Mn 0.02 Al 0.01 Sb 0.006 O 2 ), 0.47gCaO and 1.0g ZrO 2 Put it into a high-speed mixer and mix it evenly to form a mixed material. 1.03 Ni 0.924 Co 0.04 Mn 0.02 Al 0.01 Sb 0.006 O 2 , CaO and ZrO 2 The molar ratio is 1:0.002:0.002. The speed of the high mixer is 1000r / min, the mixing time is set to 20min, and the mixing is performed twice.

[0106] (4) The mixture was heated to 700°C at a heating rate of 2.5°C / min in an oxygen atmosphere and kept at this temperature for 8 hours. The calcined product was sieved to obtain 0.3 wt% CaZrO 3 Coated composite positive electrode material.

[0107] Experimental example

[0108] The composite positive electrode materials of each embodiment and comparative example are respectively prepared into lithium ion batteries, comprising the following steps:

[0109] The composite positive electrode materials of the above-mentioned embodiment and comparative example are used as positive electrode active materials to prepare positive electrode sheets. The positive electrode material layer in the positive electrode sheet contains the composite positive electrode material, PVDF and SP-Li, and the mass ratio of the composite positive electrode material to PVDF and SP-Li is 90:5:5. The negative electrode is a commercial lithium metal negative electrode. The diaphragm is a polypropylene microporous diaphragm. The electrolyte contains ethylene carbonate, ethyl methyl carbonate and LiPF 6 Ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7 to prepare a carbonate mixture, and LiPF was added to the carbonate mixture. 6 , making LiPF 6 The concentration of is 1 mol / L to prepare the electrolyte.

[0110] The electrochemical performance of the batteries prepared from the composite positive electrode materials of the above-mentioned embodiments and comparative examples was further tested. The test conditions were LR 2032, the capacity test was 0.1C charge and 0.1C discharge, 2.5-4.3V, vs. Li + / Li; Cycle test: 1C charge and 1C discharge at 45°C, 2.7~4.25V vs.Li + / Li.

[0111] The residual alkali test method of the composite positive electrode material includes: ① After weighing 5g of the composite positive electrode material in a beaker, add 100ml of distilled water. ② After sealing, magnetic stirring for 5min, the speed is controlled at 400-600r / min, ③ After stirring, collect the filtrate through slow filter paper. ④ Place the collected filtrate cup in a potentiometric titrator for testing.

[0112] The electrochemical performance test results of the batteries of various embodiments and comparative examples are shown in Table 1.

[0113] Table 1 Electrochemical performance test results of the battery

[0114]

[0115] It can be seen from Table 1 that compared with Comparative Examples 2-3, the discharge specific capacity and capacity retention rate of the composite positive electrode material of Examples 1-2 have obvious advantages, indicating that liquid phase coating can improve the first efficiency and discharge specific capacity, and at the same time, liquid phase coating achieves uniform coating, thereby improving the cycle performance.

[0116] Compared with comparative examples 1-3, the residual alkali in the positive electrode material of examples 1-6 is significantly reduced, indicating that liquid phase coating can effectively remove the residual alkali.

[0117] Compared with comparative examples 1-3, the cycle performance of the composite positive electrode material in Examples 1-6 is significantly improved, indicating that the coating layer formed by liquid phase coating can slow down the side reactions on the surface of the material and improve the thermal stability and cycle performance of the positive electrode material.

[0118] In summary, the preparation method of the composite positive material of the present invention is to wash the base material with a mixed solution containing perovskite phase elements, and while removing the residual alkali by washing, the perovskite phase is evenly coated, which stabilizes and protects the surface of the base material, and can improve the thermal stability and cycle performance of the composite positive material.

[0119] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite positive electrode material, characterized in that: It comprises a base material and a perovskite phase coating layer coated on the surface of the base material; The chemical formula of the matrix material includes LiNi x Co y Mn 1-x-y-z M z O2, wherein 0.8≤x<1, 0≤y<0.2, 0≤z<0.2, x+y+z<1, and M includes at least one of Al, Sb, Sn, B, Na, Mg, Ca, Ti, V, Zn, Si, Sr, Y, Zr, Nb, Mo, Ta, W, La, Pr, Nd, and Eu; The chemical formula of the perovskite phase coating layer includes AQO3, A is at least one of Ca, Sr and Ba, and Q is Ti or Zr.

2. The composite positive electrode material according to claim 1, characterized in that: The mass of the perovskite phase coating layer accounts for 0.1% to 5% of the mass of the composite positive electrode material; and / or The particle size D50 of the matrix material is 5 to 16 μm.

3. The composite positive electrode material according to claim 1, characterized in that: The capacity retention rate of the battery prepared from the composite positive electrode material after 50 cycles at 45° C., 1C charge and discharge, and 2.5-4.25V is greater than or equal to 94.5%.

4. A method for preparing a composite positive electrode material, characterized in that: The following steps are involved: Obtain a mixture of nickel-cobalt-manganese hydroxide, a compound of element M, and a lithium source, wherein the element M source includes at least one of Al, Sb, Sn, B, Na, Mg, Ca, Ti, V, Zn, Si, Sr, Y, Zr, Nb, Mo, Ta, W, La, Pr, Nd, and Eu; Performing a first heat treatment on the mixed material to obtain a matrix material; Obtaining a mixed solution of a compound of element A, a compound of element Q, and water, wherein A is at least one of Ca, Sr, and Ba, and element Q is Ti or Zr; The mixed solution is mixed with the matrix material, and the solid-liquid separation is performed, and the solid is collected and subjected to a second heat treatment.

5. The method for preparing a composite positive electrode material according to claim 4, characterized in that: The chemical formula of the nickel-cobalt-manganese hydroxide is Ni x Co y Mn 1-x-y-z R z (OH)2, 0.8≤x<1, 0≤y<0.2, 0≤z<0.2, x+y+z<1, R comprises at least one of Al, Y, B, Mg, Ti, Zr, Si, Nb, Mo and La; and / or The molar ratio of the nickel-cobalt-manganese hydroxide, the lithium source and the compound of the element M is 1:(1-1.1):(0.005-0.02).

6. The method for preparing a composite positive electrode material according to claim 4, characterized in that: The first heat treatment includes a first calcination and a second calcination performed sequentially; the temperature of the first calcination is 450-600°C, and the constant temperature time is 3-9h; the temperature of the second calcination is 650-800°C, and the constant temperature time is 10-20h; the heating rates of the first calcination and the second calcination are independently 1.5-5°C / min; the first heat treatment is carried out under an oxygen-containing atmosphere.

7. The method for preparing a composite positive electrode material according to claim 4, characterized in that: Contains at least one of the following features (1) to (4): (1) The mass ratio of the total mass of the compound of element A and the compound of element Q to the matrix material is (3-8):500; (2) The mass ratio of the compound of element A, the compound of element Q and water is (1.2-3):(1-6):(180-220); (3) the compound of element A comprises at least one of a nitrate and an acetate of element A; (4) The compound of element Q includes at least one of an inorganic compound of element Q and an acetate.

8. The method for preparing a composite positive electrode material according to claim 4, characterized in that: Contains at least one of the following features (1) to (4): (1) The time for mixing the mixed solution and the matrix material is 10 seconds to 30 minutes; (2) The temperature of the second heat treatment is 500-800° C., the heating rate is 1.5-6.0° C. / min, and the constant temperature time is 1-8 hours; (3) The second heat treatment is performed under an atmosphere containing oxygen; (4) Before the second heat treatment, the solid matter is dried at a temperature of 60 to 200° C. and for a time of 1 to 6 hours.

9. A battery, characterized in that: A composite positive electrode material comprising the composite positive electrode material according to any one of claims 1 to 3, or a composite positive electrode material prepared by the method for preparing a composite positive electrode material according to any one of claims 4 to 8.

10. An electrical device, characterized in that: A battery comprising the battery of claim 9.

Citation Information

Cited By

  • Layered positive electrode material of sodium-ion battery, preparation method of layered positive electrode material and sodium-ion battery

    CN120709349A

  • Preparation method of modified lithium cobalt oxide positive electrode material with high-temperature stability

    CN120943305A